From “cure” to recognition: the right of transgender people to exercise identity and gender expresion through public health services - Lengua Parra, Adrián (2016)
For many years trans people have been treated as suffering from some pathology, proposing various curative treatments as a solution to their alleged health problem. However, recent studies show that gender identity of people is a very personal and diverse characteristic so must be protected. In this article, the author explains how an understanding of gender identity that is respectful of human rights involves rethinking the State’s view of transgender people. This change of perspective requires discarding the pathological vision and opting for a system that will equip them with the necessary tools to develop their identity and avoid discrimination.